Tinjauan Semantik Naskah Nazm Waraqat Karya Shaikh Syarif Al-Din Yahya Al-'Imriti Koleksi Surau Simaung, Sumatra Barat - Sari, Aura Mustika; Maulani, Abdullah; Suparno, Darsita (Jumantara: Jurnal Manuskrip Nusantara, 2025)
This research aims to translate the book Nazm Waraqat by Shaikh Syarif al-Din Yahya al-'Imriti (890 H), from the Surau Simaung collection, West Sumatra, using the semantic translation method. The purpose of this study is to understand the application of the semantic method in the translation process, the translation techniques used, and to produce a better translation. This study has used descriptive qualitative method. The results show that the application of the semantic method is effective in maintaining the meaning, nuances, and original style of the source text while preserving the poetic style of the nazm (verse). The manuscript analysis found 145 copying errors, including additions, omissions, alterations, and substitutions, indicating the importance of editing the manuscript prior to translation. The use of Molina and Albir's translation techniques, such as borrowing and amplification successfully addressed the challenges in translating specific terms in Usul al-Fiqh. A comparison with previous translations reveals that the semantic method is more accurate in conveying the original meaning and preserving the nazm style. more effective in translating Kitab Nazm Waraqat, as it conveys the original meaning while preserving the characteristics of the nazam. This research results in an improved translation and contributes to the preservation of ancient Islamic Nusantara manuscripts.